Participation of Muslim Female Students in Online Education: A Survey - Mayurakshee Gangopadhyay; Shreyosi Chatterjee; Rini Patra; Jayita Ash; Sanjana Sarkar (UIN Sunan Gunung Djati Bandung, 2022)
Contemporary India is a primitive, patriarchal society of various feudal tribes. When we refer to caste in Considering the education system to be secular in the sense, when dealing with minority participation, we must bear in mind the debate expressed by Irfan Ahmed that â€œthe characterization of minorities is not just numbers but a comparative and powerless position vis-a-vis the majority community in a given governmentâ€ . Socio-religious issues dominate the understanding of minority female students and their participation in the education system while the existing considerations are subject to the internal affairs of the state; The current social conditions affected by the pandemic have changed and forced these conditions to be watched out for in order to create a global education system. Using qualitavie and survey research methods. This study aims to take advantage of this global space to investigate the participation status of Muslim female students and to identify areas for improvement.